The development of METAKU to support learning in hypermedia environment - Rahman, Saemah; Yassin, Siti Fatimah; Sheik Said, Normahdiah (World Scientific and Engineering Academy and Society, 2009)
The development of learning skills is not given attention in many classrooms in all levels of education in our education system today. We assume that students will be able to develop their own learning skills. The challenges students face in hypermedia learning environment need to be considered to help them learn effectively in this type of learning environment. METAKU is developed to assist students to apply metacognitive learning strategies, that is, planning, monitoring and evaluation during the learning process in hypermedia learning environment. This paper discusses the development of METAKU which employed the first three stages of a generic instructional design model - ADDIE which consists of the following stages: 1)Analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation. In the analysis stage, the data was collected using a triangulation method done concurrently: a survey of student’s preference of studying online versus offline; a focus group interview to identify challenges they face and strategies they use whilst accessing and studying the hypertext materials; and a record of student’s interaction with the computer using captivation software. A total of 240 second year university students in two public universities in Malaysia were involved in this study. The analysis stage provides information for stage 2 and 3 where the data collected was used in formulating the content and design of METAKU. It is hoped that METAKU will be able to help students develop learning skills in hypermedia learning environment.